A SNEAK PEEK INTO LIGETI’S MAILBOX: "IL ME FERA GRAND PLAISIR D’ÉCRIRE UN QUATUOR À CORDES POUR LES ARDITTI. MAIS QUAND? ..." - ŢIPLEA TEMEŞ, Bianca (Studia Universitatis Babes-Bolyai Musica, 2014)
Ligeti’s manuscripts at the Sacher archive in Basle continue to provide new insights into the composer’s life and career, elements which are meant to complement the general knowledge about this fascinating musician. The verbal sketches of two more String Quartets (Nos. 3 and 4) challenge the researcher to step into the intricate maze of Ligeti’s creative mind. Meant for two famous ensembles, the Arditti and Kronos, respectively, the sketches of the two uncompleted pieces span almost two decades, from mid-1980s until the year 2000. Remaining an unrealised dream, along with other works, such as the operas Alice's Adventures in Wonderland, The Tempest and the orchestra piece Labyrinth, the String Quartets Nos.3 and 4 represent a window into Ligeti’s laboratory, allowing us to glimpse, through fragmentary clues, the author’s secret ingredients, ideas and creative mechanisms.